2018
DOI: 10.3390/ijms19051406
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Purification of NR4A2 (Nurr1) Identified Poly(ADP-Ribose) Polymerase 1 as a Prime Coregulator in Human Adrenocortical H295R Cells

Abstract: Aldosterone is synthesized in zona glomerulosa of adrenal cortex in response to angiotensin II. This stimulation transcriptionally induces expression of a series of steroidogenic genes such as HSD3B and CYP11B2 via NR4A (nuclear receptor subfamily 4 group A) nuclear receptors and ATF (activating transcription factor) family transcription factors. Nurr1 belongs to the NR4A family and is regarded as an orphan nuclear receptor. The physiological significance of Nurr1 in aldosterone production in adrenal cortex ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For tissue-specific regulation of ChREBP activity, further analysis of the molecular mechanisms of ChREBP regulation in each tissue is required. Given that transcription factors generally form transcriptional coregulator complexes in a tissue-specific manner [64][65][66][67], it would be of interest to search for such protein complexes which ChREBP forms using a proteomic approach [67][68][69][70][71], and to determine whether these complexes could be a potential drug target for tissue-specific ChREBP activation/ inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…For tissue-specific regulation of ChREBP activity, further analysis of the molecular mechanisms of ChREBP regulation in each tissue is required. Given that transcription factors generally form transcriptional coregulator complexes in a tissue-specific manner [64][65][66][67], it would be of interest to search for such protein complexes which ChREBP forms using a proteomic approach [67][68][69][70][71], and to determine whether these complexes could be a potential drug target for tissue-specific ChREBP activation/ inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The RIME experiments were performed as reported previously [ 50 ]. Briefly, 5 × 10 7 cells were stimulated with DHT for 8 hours and then fixed in 1% formalin for 8 minutes at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are few reports on the analysis of transcriptional activation complexes in the adrenal gland for both NGFIB and NURR1, and the details of transcription factor complexes that may affect gene expression, such as CYP11B2 , still remain unknown. In 2018, we identified poly (ADP-ribose) polymerase 1 (PARP1) as a transcription factor complex of NURR1 in H295R cells [ 52 ] ( Figure 5 ). This is an in vitro study, but it could contribute to our understanding of the unknown transcription factor complex of NURR1.…”
Section: The Pathogenesis and Molecular Mechanisms Of Aldosterone Overproduction In Aldosterone-producing Adenoma (Apa)mentioning
confidence: 99%
“…Among them, NURR1 is a nuclear receptor whose expression increases when the intracellular calcium concentration transcriptional activity increases. NURR1 also interacts with PARP1 to regulate the transcriptional activity of target genes [ 52 ]. In vitro, it has been reported that inhibitors of PARP1 suppress aldosterone secretion by suppressing the expression of HSD3B1 and CYP11B2 [ 52 ].…”
Section: The Pathogenesis and Molecular Mechanisms Of Aldosterone Overproduction In Aldosterone-producing Adenoma (Apa)mentioning
confidence: 99%
See 1 more Smart Citation